2021
DOI: 10.1111/jcpp.13409
|View full text |Cite
|
Sign up to set email alerts
|

Depicting the composition of gut microbiota in children with tic disorders: an exploratory study

Abstract: Background: Symptom improvement in children with tic disorder (TD) following fecal microbiota transplantation led us to investigate the gut microbiota in TD. This exploratory study aims to depict the gut microbial profile in patients with TD and explore the impact of dopamine receptor antagonist (DRA) drugs on the composition and metabolic function of the gut microbiota. Methods: The gut microbiota were profiled in fecal samples of 49 children with TD and 50 matched healthy controls (HC) using shotgun metageno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 42 publications
1
38
0
Order By: Relevance
“…Furthermore, P. cinnamivorans, A. furcosa, B. breve , and A. finegoldii were negatively correlated in the network analysis with R. lactaris , recently renamed Faecalicatena lactaris , a member of Clostridium cluster XIVa, a mucin-degrading commensal [ 39 ] that was strongly enriched in 6-OHDA+CFX mice. Although there is a lack of a well-defined role for R. lactaris , some studies associate its enrichment with both chronic gut inflammatory disease and neurodevelopmental disorders [ 40 , 41 , 42 ], suggesting a pro-inflammatory potential for this bacterial species. Here, we can speculate that the increase of R. lactaris in dual-insulted mice can compensate for the decrease of butyrate production bacterial networks by reinforcing mucus glycoprotein degradation and that this activity is detrimental to gut barrier integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, P. cinnamivorans, A. furcosa, B. breve , and A. finegoldii were negatively correlated in the network analysis with R. lactaris , recently renamed Faecalicatena lactaris , a member of Clostridium cluster XIVa, a mucin-degrading commensal [ 39 ] that was strongly enriched in 6-OHDA+CFX mice. Although there is a lack of a well-defined role for R. lactaris , some studies associate its enrichment with both chronic gut inflammatory disease and neurodevelopmental disorders [ 40 , 41 , 42 ], suggesting a pro-inflammatory potential for this bacterial species. Here, we can speculate that the increase of R. lactaris in dual-insulted mice can compensate for the decrease of butyrate production bacterial networks by reinforcing mucus glycoprotein degradation and that this activity is detrimental to gut barrier integrity.…”
Section: Discussionmentioning
confidence: 99%
“…6 ), the larger landmark nodes can be divided into three categories: population, research methods, and detection methods. A large number of studies have been conducted on the relationship between age (newborn [ 45 ], infant [ 46 ], child [ 47 ], teenager [ 48 ], adult [ 49 ], middle aged [ 50 ] and aged [ 51 ]), gender (male [ 52 ] and female [ 53 ]) and population groups and gastrointestinal microorganisms. This may be related to researchers finding that the gastrointestinal floras of different populations are significantly different, which requires classification to further study the topic.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, exercise-induced stress behavior also caused changes in the abundance of Ruminococcus gnavus, which also modulates intestinal mucus degradation and immune function [ 107 ]. Recent results from metagenomic analysis via shotgun sequencing of fecal samples from 49 children with a tic disorder (TD) and 50 matched healthy controls showed that gut microbiota from TD subjects had a higher abundance of Ruminococcus lactaris and Ruminococcus gnavus [ 108 ]. Clinical evidence also supports a dysregulation in dopamine levels in TD, though the exact effect on dopaminergic neurons, receptors, and transporters is less clear [ 109 ].…”
Section: Gut Microbes Effects On Dopaminementioning
confidence: 99%